Multifunctional storage with table and chair/ Wan Muhammad Hilmi Wan Ibrahim - Wan Ibrahim, Wan Muhammad Hilmi (2015)
Nowadays, people seek for furniture that has many functions. Function, design, space, price and material used are important features that need to be considered by customers. Lack of space is the limitation for people who are living in small houses; hence, there is a need for multifunctional furniture. This study is conducted to overcome those problems by designing multifunctional storage with table and chair. The main concept is designing not only multipurpose furniture, but also can be sold in an economical price. In this study, the bookshelves can be switched to a coffee table and chair. Furthennore, modem and contemporary design was applied. Blockboard was used as the main material, as they have excellent properties, cheap and good appearance. A set of a questionnaires were distributed to hundreds of respondent which consists of student, lecturers and others. Then the data was analysed by using SPSS to acquire the result. Results show that the correspondent gives a positive feedback regarding on the material used, multifunction and suitable for limited space. Overall, this multifunctional storage with table and chair is suitable to commercialize in market.